Operation of the 400-750kV pulse voltage multi-cascade discriminator - Zubetz, V.N.; Derbilov, V.I.; Esin, S.K.; Klenov, V.S.; Nikulin, E.S.; Frolov, O.T.; Yakushev, V.P. (Вопросы атомной науки и техники, 1999)
The multi-cascade discriminator (МD) of the amplitude of pulsed 400-750kV voltage is an important part of the pulse high-voltage generator at the highcurrent linac injector of the Moscow meson factory [1]. It was invented and designed at the Efremov Institute of Electrophysical Apparature (Leningrad). It was partially tested at the factory [2] and successfully ran at 1 Hz repetition rate [3] in the adjusting mode of the accelerator. However the transition to 50Hz repetition rate gave rise to certain drawbacks, such as the current overloading of the inductivities, breakdown of the diodes and insufficient voltage. Analytical and experimental researches were conducted, and the required changes were made on their basis. These changes allowed the discriminator to operate with high reliability. The main results are set forth in this report.